Eating Insects and Italian Gastronomy - Bordenca, Ilaria Ventura (E|C, 2025)
What happens in the culinary field when a new food appears – and with it a new taste – within a cultural system? How does the system react? What resources does it activate to make sense of and bridge the gap of difference and strangeness? We will examine the case of an ambitious attempt at major change: bringing insects to the plates of Italians. We will address these issues by dealing with specific cases of media and brand communication around the use of insect meal in the Italian market, where the consumption of foods based on crickets, locusts, larvae, is practically non-existent.